THE EXISTENCE OF THE ELECTION SUPERVISORY AGENCY AS AN INDEPENDENT INSTITUTION IN HANDLING ADMINISTRATIVE VIOLATIONS IN THE ELECTIONS OF GOVERNOR, REGENT AND MAYOR - Martadilla, Metri; Ardilafiza; Satmaidi, Edra (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
In the design of the Local Leaders Election Law, the Provincial and Regency/City Election Supervisory Agency are positioned as part of the process for resolving administrative violations, specifically by issuing recommendations. While, the resolvents are the Provincial and the Regency/City General Elections Commission, namely following up on the recommendations of the Provincial and the Regency/City Election Supervisory Agency regarding findings and reports of election violations. In practice, the recommendations given by the Election Supervisory Agency to the General Elections Commission are often ignored, so that the recommendations of the Election Supervisory Agency are often legally meaningless. This affects the existence of Election Supervisory Agency in exercising its authority to handle administrative violations of the Local Leaders Election. The problems studied are: how is the handling of administrative violations in the Election of Governors, Regents and Mayors by the Election Supervisory Agency and how is the existence of the Election Supervisory Agency as an Independent Institution in handling administrative violations in the Election of Governors, Regents and Mayors. This research was normative legal research focusing on the study of laws and regulations governing the handling of administrative violations of the Local Leaders Election using primary, secondary and tertiary legal materials. The results of the study show that Election Supervisory Agency 's authority is limited by the Regional Election Law, which states that the authority to complete the process of handling administrative violations is through a clarification and study process, the results of which are in the form of recommendations to the General Elections Commission and the General Elections Commission is required to follow up by preparing a legal review by paying attention to the fulfilment of the elements of the existence of administrative election violations, which is then held in a plenary meeting to examine and decide on the follow-up actions for the administrative election violations. Therefore, the existence of the Election Supervisory Agency as an independent institution is slightly weakened in the process of organizing Local Leaders Election.